Microsatellite instability in the inflamed and non-neoplastic colonic mucosa in ulcerative colitis [Ülseratif kolitli hastalarin non-neoplastik inflame kolonik mukozalarinda mikrosatellit instabilitesi] - (:unkn) unknown (Marmara University, 2009)
Background and Aim: Ulcerative colilis (UC) is a chronic inflammatory disease of the colon associated with a high risk of developing colorectal cancer. There is a need for a molecular marker that would predict the colorectal cancer associated with UC. Microsalellite instability (MSI) has been detected in colorectal cancers associated with UC. Some reports in the literature show the presence of MSI in the neoplastic and non-neoplastic severe inflammatory mucosa of UC. The aim of this study was to assess whether MSI is present in non-neoplaslic mild to moderate inflamed mucosa in UC. Material and Method: Colonic inflamed mucosa samples from 29 patients were analysed for MSI using the live standard markers BAT-25, BAT-26, D2S123, D5S346, and D17S250 by a multiplex polymerase chain reaction. All tissues had inactive or mild to moderate inflammatory activities as seen histopathologically. Results: None of the non-neoplaslic inflamed colonic mucosa samples showed MSI in the five standard markers. Conclusion: This study suggests that the severity of inflammation should be taken into account when estimating MSI in UC.
Keywords: Micro-satellite instability; Ulcerative colitis